Effect of thermocycling on the tensile and shear bond strengths of three soft liners to a denture base resin - Carlos Nelson Elias; Flavio Queiroz Henriques (University of São Paulo, 2007)
STATEMENT OF PROBLEM: In clinical practice, loss of adhesion between the silicone-based denture liner and the denture base resin is always an undesirable event that might cause loss of material softness, water sorption, bacterial colonization and functional failure of the prosthesis. PURPOSE: This study evaluated the effect of thermocycling on tensile and shear bond strengths of three soft liner materials to a denture base acrylic resin. MATERIAL AND METHODS: Three resilient liners (Mucopren-Soft, Mollosil-Plus and Dentusil) and a heat-polymerized acrylic resin (QC-20) were processed according to manufacturers' directions. Sixty specimens (14 x 14 mm cross-sectional area) per bond strength test (20 for each liner) were fabricated and either stored in water at 37ºC for 24 hours (control groups; n=10) or thermocycled 3,000 times in water between 5ºC and 55ºC (test groups; n=10). The specimens were tested in tensile and shear strength in a universal testing machine until fracture. Bond strength means were compared between water-stored and thermocycled groups for each material, as well as among materials for each treatment (water storage or thermocycling). Failure mode (adhesive, cohesive and mixed) after debonding was assessed. Data were analyzed statistically by paired Student's t-test and ANOVA at 5% significance level. RESULTS: The water-stored groups had statistically significant higher bond strengths than the thermocycled groups (p<0.05). Without thermocycling, Mucopren-Soft (2.83 ± 0.48 MPa) had higher bond strength than Mollosil-Plus (1.04 ± 0.26 MPa) and Dentusil (1.14 ± 0.51 MPa). After thermocycling, Mucopren-Soft (1.63 ± 0.48 MPa) had the highest bond strength (p<0.05). CONCLUSION: The bond strength of the three soft denture liners tested in this study changed with their chemical composition and all of them exhibited higher bond strengths than those usually reported as clinically acceptable. CLINICAL IMPLICATIONS: All soft lining materials tested in this study showed a significant decrease in the bond strength to an acrylic denture base resin after thermocycling. In spite of thermocycling, though, the silicone-based liners had satisfactory bond strengths for clinical application.